PERCUTANEOUS ENDOSCOPIC GASTROSTOMY IN CHILDREN AND ADOLESCENTS: 15-YEARS’ EXPERIENCE OF A TERTIARY CENTER - FRANCO NETO,José Andrade (2021)
ABSTRACT BACKGROUND: Percutaneous endoscopic gastrostomy (PEG) is an important option for enteral nutrition for both children and adults. It is considered a safe, effective, and advantageous technique in comparison to other complementary feeding routes. It allows continuous feeding, the feeding of patients with swallowing disorders due to neurological causes or others, and the administration of non-palatable diets or medications, all with low rates of complications and mortality. OBJECTIVE: This study aimed to evaluate the main indications and complications of PEG in pediatric patients. In addition, the impact on the nutritional status of patients undergoing PEG was also compared with weight, body mass index (BMI), and height according to references from the World Health Organization. METHODS: This observational and retrospective study included 152 children and adolescents who underwent PEG between January/2003 and December/2018. Patients up to 18 years of age at the time of the procedure were included. Complications related to the procedure were classified as minor or major. Patients with PEG indication for nutritional supplementation were evaluated for weight gain, height, and BMI, using the Z score at the day of the procedure and six months, 1 year, and 2 years after the procedure. RESULTS: Indications for PEG were: swallowing disorder of neurological cause (67.1%), need for nutritional supplementation (25%), swallowing disorder of mechanical origin (6.6%), and indication of gastric decompression (1.3%). Minor complications occurred in 57.8% of patients and major complications in 9.8% of patients. The traction technique corresponded to 92.1% and puncture to 7.9%. The death rate was 1.3%. Thirty-eight patients had an indication for nutritional supplementation. In these patients, there was a gradual increase in both BMI and weight, reaching statistically significant differences (P=0.0340 and P= 0.0105, respectively). These differences were more evident in chronic renal disease patients. Height did not vary significantly (P=0.543). CONCLUSION: PEG proved to be an advantageous option as an auxiliary feeding method in pediatric patients. Dysphagia of neurological origin was the main indication followed by the need for nutritional supplementation. PEG has low frequency of major complications and mortality. This study also showed the importance of PEG in patients who need nutritional supplementation, as it enabled patients to move from undernutrition to normal weight ranges.